Proceedings of the 10th EAI International Conference on Testbeds and Research Infrastructures for the Development of Networks & 2015
DOI: 10.4108/icst.tridentcom.2015.259704
|View full text |Cite
|
Sign up to set email alerts
|

A Unified Monitoring Framework for Energy Consumption and Network Traffic

Abstract: Providing experimenters with deep insight about the effects of their experiments is a central feature of testbeds. In this paper, we describe Kwapi, a framework designed in the context of the Grid'5000 testbed, that unifies measurements for both energy consumption and network traffic. Because all measurements are taken at the infrastructure level (using sensors in power and network equipment), using this framework has no dependencies on the experiments themselves. Initially designed for OpenStack infrastructur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 14 publications
(21 reference statements)
0
10
0
Order By: Relevance
“…Experiments have also shown that by exploiting features of monitoring hardware, KWAPI can monitor a large set of resources without perturbing experiments [46]. The throughput, latency, and jitter of measuring power consumption and transferring the measurement data have also been evaluated under several conditions [45].…”
Section: Results and Lessons Learntmentioning
confidence: 99%
See 2 more Smart Citations
“…Experiments have also shown that by exploiting features of monitoring hardware, KWAPI can monitor a large set of resources without perturbing experiments [46]. The throughput, latency, and jitter of measuring power consumption and transferring the measurement data have also been evaluated under several conditions [45].…”
Section: Results and Lessons Learntmentioning
confidence: 99%
“…The KWAPI framework 3 was created to enable measuring the power consumed by cluster resources in OpenStack [45]. It has been adapted to support largescale federations of clusters [46] and is currently the solution deployed on the Grid5000 platform [47] to monitor the energy consumed by computing and network resources. Its architecture, depicted in Figure 3, relies on a layer of drivers that retrieve power measurements from several devices, and plug-ins or data consumers that collect and process the measurement data.…”
Section: Kilowatt Api (Kwapi)mentioning
confidence: 99%
See 1 more Smart Citation
“…The web portal and the API are both written in Python and leverage the "Flask" micro web framework. The API component makes an extensive use of the Swagger framework 7 which automatises the generation of complete REST web services and their documentations from a single description file (written in JSON or YAML). This choice has enabled us to focus on the definition and the implementation of the API, by reducing the quantity of required boilerplate code.…”
Section: Seduce Portalmentioning
confidence: 99%
“…On the latter challenge, many research efforts have been conducted [1] [2], most of them focusing on the implementation of on demand power management systems, such as Dynamic voltage scaling (DVFS) [3] [4] and vary-on vary-off (VOVO) [5] [6]. Some work has been made to extend existing scientific testbeds with power monitoring of experiments : for example Kwapi [7] enables researchers to track the power consumption of their experiments conducted on Grid'5000.…”
Section: Introductionmentioning
confidence: 99%